Port Byron, Sheridan County - Campbell, Lacie (Kansas State University, The Chapman Center for Rural Studies, 2015)
This study overviews the lost town of Port Byron, Kansas, from its one booming year along the Great Western Trail to its disappearance after the Union Pacific Railway came through and shut down the town. Much information has been provided by archaeologist and local historian, Don Rowlison.
Lacie Campbell, “Port Byron, Sheridan County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/152.
Keywords: Sheridan County; Port Byron; Union Pacific Railway; Hoxie; cattle drive; Great Western Trail